Progressivism Philosophy and Its Implications for 21st Century Educational Practices in Indonesia - Syammary, Naufal Akmal; Yahya, Amri; Firmansyah, Haris Furkon Hasbi; Fiddin, Rufhan; Alam, Fajar Nur Syah (LP. Ma'arif Janggan Magetan, 2024)
This study aims to analyze in depth the philosophy of progressivism and how this approach has implications for educational practice in the 21st century. This research uses a descriptive qualitative approach through the Systematic Literature Review (SLR) approach. The results of this study show that the philosophy of progressivism has exerted a significant influence on educational practice. This can be seen from the implications: 1) the application of project and inquiry-based learning methods encourages students to actively seek information, ask questions and solve problems collaboratively. In some schools, teachers implement interdisciplinary projects where students work in groups to solve real problems, such as environmental projects or simple technological innovations, 2) curricula designed to be relevant to students' lives, allowing adaptation to individual interests and needs. Mentoring program where students can choose a project or learning topic that suits their interests, accompanied by a mentor or teacher, 3) focuses on developing 21st century skills such as critical thinking, creativity, collaboration, and communication. collaborative learning through group discussions, debates, and project presentations, where students learn to work together and communicate effectively.